Differences between vaccinated and unvaccinated women explain increase in non-vaccine-type human papillomavirus in unvaccinated women after vaccine introduction. Issue 52 (19th December 2017) - Ding, Lili; Widdice, Lea E.; Kahn, Jessica A.
Abstract: The aim of this study was to determine whether an observed increase in non-vaccine-type human papillomavirus (HPV) in unvaccinated women during the first eight years after vaccine introduction may be explained by differences in demographics or sexual behaviors, instead of type replacement. We analyzed data from three cross-sectional surveillance studies of 13–26 year-old women (total N = 1180). For women recruited from a health department clinic, older age (OR = 1.4, 95% CI: 1.2–1.6) and consistent condom use with main partner in the past 3 months (OR = 11.6, 95% CI: 3.4–40) were associated with being unvaccinated. For women recruited from a teen health center African American race (OR = 0.2, 95% CI: 0.07–0.7) and having Medicaid health insurance (OR = 0.3, 95% CI: 0.1–0.7) were inversely associated with being unvaccinated. The observed increase in non-vaccine-type HPV prevalence in unvaccinated women may be explained by differences between unvaccinated and vaccinated women.